2019
DOI: 10.5296/ijhrs.v9i4.15829
|View full text |Cite
|
Sign up to set email alerts
|

Role of Public Service Motivation, Organization Values and Reward Expectation on Performance of Public Sector Employees in Henan, China

Abstract: The main objective of this study is to investigate the role of public service motivation, organization value and reward on performance of public sector employee in the Henan, China. Data is collected from adopted instrument from earlier studies. The researcher has collected data from 396 respondents by using online survey and self-administrative collection method. For analysis of data, SPSS and SmartPLS software were used. It has been concluded that role of organization values does not have a relationship with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is in support of the research undertaken previously on 35,000 federal employees of the USA, demonstrating that there is no evidence to show that PSM and job performance had any association according to a study done by Alonso and Lewis (2001). Similarly, research undertaken on Chinese public sector officials also indicated that both monetary and non-monetary factors are responsible for work performance, hence PSM alone is not sufficient enough to create higher job performance; Xu et al (2019). Henceforth the conclusion on PSM and job performance, is that there is still a lack of research to show that PSM and job performance are positively associated, since there are other mediators used to establish this relationship, and as argued by Ritz et al (2016) results of the studies are mostly influenced by sample size and the items used, and more robust measures are still needed.…”
Section: Pgjsrtmentioning
confidence: 99%
“…This is in support of the research undertaken previously on 35,000 federal employees of the USA, demonstrating that there is no evidence to show that PSM and job performance had any association according to a study done by Alonso and Lewis (2001). Similarly, research undertaken on Chinese public sector officials also indicated that both monetary and non-monetary factors are responsible for work performance, hence PSM alone is not sufficient enough to create higher job performance; Xu et al (2019). Henceforth the conclusion on PSM and job performance, is that there is still a lack of research to show that PSM and job performance are positively associated, since there are other mediators used to establish this relationship, and as argued by Ritz et al (2016) results of the studies are mostly influenced by sample size and the items used, and more robust measures are still needed.…”
Section: Pgjsrtmentioning
confidence: 99%